Predictors of upper limb disorders among a public university workers in Malaysia - Karwan, M. K.; Ariffin, Ahmad Azuhairi; Kadir @ Shahar, Hayati (Community Health Society Malaysia, 2015)
Background: Upper Limb Disorder (ULD) includes a wide range of musculoskeletal diseases and syndromes, which are usually associated with pain and discomfort. The major forms of musculoskeletal disease that account for significant work-related morbidity include upper limb disorders. The main objective of this study was to determine the prevalence and associated factors of upper limb disorders among a public university worker.